PRAKTIK MAHAR SELAIN BENDA: PERSPEKTIF USHUL FIQH TERAPAN - Nasution, Muhammad Hasan; Yuslem, Nawir; Khairi, Nispul (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2025)
Abstract:This research examines the application of non-material mahr (dower) in Islamic law through the lens of usul al-fiqh (Islamic legal theory). Mahr, as a mandatory gift from the groom to the bride in a marriage contract, is not limited to tangible assets but may also take the form of non-material benefits, such as the recitation or teaching of the Qur'an or a spiritual commitment. In contemporary Muslim communities, particularly among those who prioritize religious values and simplicity in marriage, the practice of non-material mahr has become increasingly accepted. This study employs a normative qualitative method with a juridical-theological and usul fiqh approach, using descriptive-analytical techniques based on primary sources (the Qur’an, Hadith, classical and contemporary Islamic legal texts) and secondary sources (scholarly journals and field observations). The findings indicate that non-material mahr is legally valid in Islamic jurisprudence, provided it brings benefit (maslahah), is mutually agreed upon, and does not contradict Islamic legal principles. From the perspective of usul al-fiqh, concepts such as maslahah mursalah, istihsan, and ‘urf justify and strengthen the permissibility and social relevance of non-material mahr. This form of mahr offers a practical and spiritually meaningful solution to modern marital challenges while aligning with the objectives of Islamic law (maqasid al-shari‘ah). Keywords: Mahr Non material, Usul al-Fiqh, Maslahah, Istihsan, ‘Urf Abstrak:Penelitian ini mengkaji penerapan mahar nonmateri dalam hukum Islam melalui sudut pandang ushul fiqh (teori hukum Islam). Mahar, sebagai pemberian wajib dari mempelai pria kepada mempelai wanita dalam suatu akad nikah, tidak terbatas pada harta berwujud, tetapi juga dapat berupa manfaat nonmateri, seperti pembacaan atau pengajaran Al-Qur'an atau komitmen spiritual. Dalam masyarakat Muslim kontemporer, khususnya di kalangan yang mengutamakan nilai-nilai agama dan kesederhanaan dalam perkawinan, praktik mahar nonmateri semakin diterima. Penelitian ini menggunakan metode kualitatif normatif dengan pendekatan yuridis-teologis dan ushul fiqh, dengan menggunakan teknik deskriptif-analitis berdasarkan sumber-sumber primer (Al-Qur'an, Hadits, teks-teks hukum Islam klasik dan kontemporer) dan sumber-sumber sekunder (jurnal-jurnal ilmiah dan pengamatan lapangan). Temuan penelitian menunjukkan bahwa mahar nonmateri sah secara hukum dalam yurisprudensi Islam, dengan syarat membawa manfaat (maslahah), disepakati bersama, dan tidak bertentangan dengan prinsip-prinsip hukum Islam. Dari perspektif ushul fiqh, konsep-konsep seperti maslahah mursalah, istihsan, dan ‘urf membenarkan dan memperkuat kebolehan dan relevansi sosial dari mahar non-material. Bentuk mahar ini menawarkan solusi praktis dan bermakna secara spiritual terhadap tantangan perkawinan modern sekaligus sejalan dengan tujuan hukum Islam (maqasid al-shari‘ah).Kata kunci: Mahar Non material, Usul al-Fiqh, Maslahah, Istihsan, ‘Urf